P865 Safety & efficacy of lifileucel (LN-144) tumor infiltrating lymphocyte therapy in metastatic melanoma patients after progression on multiple therapies – independent review committee data update. (15th April 2020) - Sarnaik, Amod; Khushalani, Nikhil; Chesney, Jason; Kluger, Harriet; Curti, Brendan; Lewis, Karl; Medina, Theresa; Thomas, Sajeve; Pavlick, Anna; Whitman, Eric; Algarra, Salvador; Corrie, Pippa; et al.
Abstract : Background: Treatment options are limited for patients with advanced melanoma who have progressed on checkpoint inhibitors and targeted therapies such as BRAF/MEK inhibitors (if BRAF-V600E mutated). Adoptive cell therapy utilizing tumor-infiltrating lymphocytes (TIL) has shown antitumor efficacy with durable responses in heavily pretreated melanoma patients. Safety and efficacy of lifileucel, a centrally manufactured cryopreserved autologous TIL therapy assessed by both investigator and an independent review committee (IRC), are presented. Methods: C-144-01 is a global Phase 2 open-label, multicenter study of the safety and efficacy of lifileucel in patients with unresectable metastatic melanoma. We report on Cohort 2 (N = 66) patients with Stage IIIC/IV unresectable melanoma who received lifileucel. Tumors resected at local institutions were processed in central GMP facilities for TIL production in a 22-day process. Final TIL infusion product was cryopreserved and shipped to sites. Patients received one week of cyclophosphamide/fludarabine preconditioning lymphodepletion, a single lifileucel infusion, followed by up to 6 doses of IL-2. All responses were assessed by RECIST 1.1. Results: 66 patients had the following baseline characteristics: 3.3 mean prior therapies (anti-PD1 100%; anti-CTLA-4 80%; BRAF/MEK inhibitor 23%), relatively high tumor burden (106 mm mean target lesion sum of diameters), 44% with liver and/or brain lesions, median LDH 244 U/L. Objective Response Rate (ORR) by investigator was 36.4% (2 CR, 22 PR, 1 previously confirmed PR is now changed to SD) and Disease Control Rate (DCR) of 80.3%. At a median follow up of 9.7 months, median Duration of Response (DOR) has not been reached. The adverse event profile was generally consistent with the underlying advanced disease and the profile of the lymphodepletion and IL-2 regimens. The ORR per IRC was 34.8% (2 CR, 21 PR) and DCR was 72.7%. At a median follow up of 6.9 months, the median IRC DOR has not been reached. Overall concordance rate of investigator and IRC read of response was 89.4%. The concordance compares favorably with literature reports in a metastatic disease. 1 Conclusions: Lifileucel treatment resulted in a 36.4% ORR in heavily pretreated metastatic melanoma patients with high baseline disease burden who had received prior anti-PD1 and BRAF/MEK inhibitors, if tumor BRAF mutated. The high concordance of 89.4% between investigator and IRC confirms the original assessment of lifileucel efficacy in metastatic melanoma. 2 Acknowledgements: The authors would like to thank the patients and their families for participation in the study. The authors would also like to acknowledge the support and dedication of all investigators and site team members from all participating clinical trial institutions. Trial Registration: ClinicalTrials. gov Identifier: NCT02360579 Ethics Approval: Ethics Approval This trial was approved by Western Institutional Review Board - IRB Tracking Number: 20160198. References: Ghiorghiu DC, et al. Comparison of central and site review of RECIST data in an open randomised phase II trial in advanced melanoma. 10.1594.ecr 2009/C-075. Sarnaik A, et al. Safety and efficacy of cryopreserved autologous tumor infiltrating lymphocyte therapy (LN-144, lifileucel) in advanced metastatic melanoma patients who progressed on multiple prior therapies including anti-PD-1. J Clin Oncol 2019;37:2518–2518.